2017
DOI: 10.1371/journal.pone.0169663
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal Procrustes Analysis for Dictionary Learning in Sparse Linear Representation

Abstract: In the sparse representation model, the design of overcomplete dictionaries plays a key role for the effectiveness and applicability in different domains. Recent research has produced several dictionary learning approaches, being proven that dictionaries learnt by data examples significantly outperform structured ones, e.g. wavelet transforms. In this context, learning consists in adapting the dictionary atoms to a set of training signals in order to promote a sparse representation that minimizes the reconstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…The processing effects of the three algorithms were compared when the noise ρ was 10, 30, 50, and 70, respectively. The results showed that the PSNR and SSIM values of N-KSVD dictionary after denoising were both greater than those of DCT dictionary, and the differences were statistically significant, which indicated that N-KSVD dictionary had the best denoising effect, in line with the research results of Grossi et al [ 30 ]. Subsequently, N-KSVD dictionary was used in the diagnosis of patients, and the test group and the control group were compared for basic information.…”
Section: Discussionsupporting
confidence: 85%
“…The processing effects of the three algorithms were compared when the noise ρ was 10, 30, 50, and 70, respectively. The results showed that the PSNR and SSIM values of N-KSVD dictionary after denoising were both greater than those of DCT dictionary, and the differences were statistically significant, which indicated that N-KSVD dictionary had the best denoising effect, in line with the research results of Grossi et al [ 30 ]. Subsequently, N-KSVD dictionary was used in the diagnosis of patients, and the test group and the control group were compared for basic information.…”
Section: Discussionsupporting
confidence: 85%
“…Recently, sparse representation has been extensively used for applications such as compressed sensing, reconstruction, and de-noising of medical images [46]. However, there are limited studies for sparse bio-signals de-noising [47]. These methods assume that the natural signal are sparse on to either a fixed dictionary like the Fourier and wavelet transform or a learned dictionary [48].…”
Section: Introductionmentioning
confidence: 99%
“…The feature space is obtained employing deep features coupled with the linear discriminant analysis, while the concise model is derived adopting the method of optimal directions (MOD) [13], which has proved to be very efficient for low-dimensional input data. The benefits of this approach is that, contrarily to generic learning algorithms [14], the label consistency between dictionary atoms and training data is maintained, allowing the direct application of the classification stage based on majority voting (a demo code is available on the website: ).…”
Section: Introductionmentioning
confidence: 99%